The production of digital videos as a possibility for evaluative practice (Revista BOEM, 2024)
The objective of this essay on videos as an evaluation tool is to present the production of digital videos as a possibility for evaluative practice in teaching degree courses. Based on the experience gained through the teaching internship developed by the Program for Improvement and Support of Teaching in Higher Education (PAADES) at the São Paulo State University, Rio Claro/SP campus, we worked with a group of Mathematics students from the aforementioned institution, following the process of producing videos with mathematical content by the students and the subsequent presentation of their productions. These videos were evaluated andcontributed to the final grade of the course. As results, we highlight the participation, creativity, and engagement of the students in the video production process. We consider that, more than just a form of evaluation, this activity demonstrates the importance of how mathematical content can be presented, as well as how mathematical learning is constituted when students participate in learning collectives. Furthermore, this practice contributes to changing the public image of Mathematics.
Keywords: digital videos; evaluative practice; teaching internship; public image of mathematics